SURFACE HEAT ISLANDS: FREQUENCY OF SPATIAL INTENSITY AND VARIABILITY IN A CITY WITH A CONTINENTAL TROPICAL CLIMATE - Costa Trindade Amorim, Margarete Cristiane de [UNESP] (Univ Estado Rio Janeiro, 2019)
The purpose of this article was to analyze the spatial distribution of target temperatures and the frequency of surface heat island intensities in areas with characteristics relating to land use, vegetation cover, densities and different construction patterns in Presidente Prudente, SP. The procedures adopted consisted of the use of 24 images of the Landsat 8 satellite, band 10, available and without cloud cover, between February 2013 and January 2016. The results showed that the higher frequency of high intensities of surface heat islands was recorded in a housing complex with a low building standard, followed by a neighborhood with a medium building standard. The areas with the lowest building density and presence of permeable soils with ground cover and tree cover were the ones that presented the highest frequency of low intensities of surface heat islands or fresh islands. The spatial variability of surface temperatures in the neighboring urban and rural environment results from the physical characteristics of the targets (types of building materials, soil waterproofing, density of buildings, and vegetation). These characteristics, resulting from the urbanization process, may cause the poorest, and therefore, most vulnerable, population to be more susceptible to situations of thermal discomfort and health problems.
Keywords: surface heat island; spatial variability; land use; remote sensing; Landsat 8